The importance of rehabilitation in Parkinson’s disease in the patients’ evaluation - Przeszłowska, Joanna (European Journal of Clinical and Experimental Medicine, 2010)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The aim of the thesis: The aim of the thesis mu the physical rehabilitation appraisal as Hell as as-sessment of the significance of the physical rehabilitation in Parkinson k disease in patients 'rating. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Materials and methods: In the study, 47 patients stere analyzed utth identified Parkinson's disease. Among them 23 patients from Rzeszow 24 patients from associations for patients with Parkinsons' dis-ease. In the research the author's questionnaire and the Weber-Rating Scale here used. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The results: As it can be seen from the analysis, the physical rehabilitation in the patient rating has a great importance in the Parkinson disease treatment. The age of patients and the time of the disease have an influence on the estimation of the physical rehabilitation. It has no relation to the gender, place of residence, educational background, civil status and the degree of the Parkinson disease that sou es-timated by the Weber scale. The patients from the associations indicate the greater meaning of the phys-ical rehabilitation. They gave greater evaluation of the rehabilitation in comparison to patients from Rzeszow <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The physical rehabilitation has got an unquestionable importance in medical treat-ment of the Parkinson disease. The rehabilitation appraisal depends on the age and the time of the dis-ease. The institutions like patients' associations are helpful in supplying information and provide better access to rehabilitation for the sick